2018
DOI: 10.1111/den.13051
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Charlson comorbidity index and prognostic nutritional index on prognosis in patients with early gastric cancer after endoscopic submucosal dissection

Abstract: CCI and PNI can be prognostic indicators for non-elderly and elderly patients with EGC after ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 25 publications
3
56
0
1
Order By: Relevance
“…However, a poorer prognosis is anticipated in patients with severe comorbidities even if successful treatment is achieved. Recently, results similar to ours were reported [8,10,11]. One multicenter retrospective cohort study [8], using propensity score analysis, demonstrated that 5-year overall survival rates of patients with liver cirrhosis was 60.0%, which was significantly lower than that of patients without liver cirrhosis (91.0%).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…However, a poorer prognosis is anticipated in patients with severe comorbidities even if successful treatment is achieved. Recently, results similar to ours were reported [8,10,11]. One multicenter retrospective cohort study [8], using propensity score analysis, demonstrated that 5-year overall survival rates of patients with liver cirrhosis was 60.0%, which was significantly lower than that of patients without liver cirrhosis (91.0%).…”
Section: Discussionsupporting
confidence: 84%
“…In addition, ESD has also been performed on patients with severe comorbidities, such as liver cirrhosis or renal dysfunction, as well as in elderly patients because it is less invasive [8,9]. Some studies [10,11] have also reported on the long-term outcome of gastric ESD for patients with severe comorbidities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify risk factors for heart disease, including previous hypertension, diabetes, and dyslipidemia, we used algorithms (which were similar to previously reported algorithms in a study that used NHIS data) along with ICD‐10 codes (hypertension, I10‐I13 and I15; diabetes mellitus, E11‐E14; and dyslipidemia, E78) in combination with the electronic data interchange code of related medications . The Charlson Comorbidity Index was also evaluated with an ICD‐10 code . Lifestyle factors (eg, smoking and obesity) were not included in this analysis because the NHID does not provide this information.…”
Section: Methodsmentioning
confidence: 99%
“…13 The Charlson Comorbidity Index was also evaluated with an ICD-10 code. 16 Lifestyle factors (eg, smoking and obesity) were not included in this analysis because the NHID does not provide this information.…”
Section: Variables and Operational Definitionsmentioning
confidence: 99%